Urban Governance and Social Services Delivery in Nigeria’s Intermediate Cities: Policy Implications - Ogbuefi, Paul Chibueze; Stanley, Nwaogu Chika; Grace, Ugwu Chidubem; Obineme, Chinaza Henry; Jiburum, Uloma; Nwachukwu, Maxwell Umunna (Journal of Ecohumanism, 2025)
This study examined urban governance and its effects on social services delivery in the city of Enugu. Data used in this study were collected from primary sourcethrough a questionnaire method from 60 respondents who reside in Enugu and Owerri cities. Mean and standard deviation was used in analyzing the data. The mean score results indicate that there is a poor observance of six good governance principles, namely, accountability (2.4), openness to change(2.3), compliance with the law (2.4), subsidiarity (2.4), absence of corruption(2.3) and equality(2.4) by government in the provision of social services in Enugu. This implies the existence of bad governance in the city’s administration of social services delivery. However, the other good governance principles namely, transparency (2.5), efficiency and effectiveness (2.5), innovation (2.6), consensus-oriented (2.6), responsiveness (2.6), integrity (2.7), democratic representation (2.8), security (2.8) and cultural diversity (2.9) show moderate observance by the government in the provision of social services. The residents have poor access to social services delivery in areas of potable water supply (1.5), affordable public housing (1.9), recreational services (2.1), efficient effective mass transport system (2.2) and efficient security services (2.2). In addition, bureaucracy, corruption, mismanagement, lack of transparency, lack of political continuity and violation of acceptable norms are the key factors that cause poor social services delivery. A comparative analysis between Enugu and Owerri indicates interesting results, evidence of good urban governance is more pronounced in Enugu than in Owerri, residents of Enugu have more access to efficient social services delivery than Owerri.